Feasibility Analysis of Phenotype Quantification from Unstructured Clinical Interactions. Issue 1 (11th January 2022) - Barron, Daniel S.; Heisig, Stephen; Agurto, Carla; Norel, Raquel; Quagan, Brittany; Powers, Albert; Birnbaum, Michael L.; Constable, Todd; Cecchi, Guillermo; Krystal, John H.
We conducted a feasibility analysis to determine the quality of data that could be collected ambiently during routine clinical conversations. We used inexpensive, consumer-grade hardware to record unstructured dialogue and open-source software tools to quantify and model face, voice (acoustic and language) and movement features. We used an external validation set to perform proof-of-concept predictive analyses and show that clinically relevant measures can be produced without a restrictive protocol.